Bersekongkol Membubarkan Komisi Pemberantasan Korupsi - Cicik Nawang Putri; Helmi Alwi; Budi Suharto (ADALAH, 2020)
Abstract:The purpose of this study is to determine the legal implications of the loss of the authority to investigate and prosecute and the responsibility of the leadership of the Corruption Eradication Commission (KPK). In this study using empirical research methods. This researcher offers something new, namely the weakening of the KPK institutions which has an impact on the less than optimal performance of corruption eradication and even results in the cessation of efforts to investigate, investigate and prosecute various corruption cases, which could have implications for the dissolution of the KPK institutions. The results of this study stated that the loss of the authority to investigate and prosecute and the responsibilities of the KPK leadership resulted in a decline in KPK performance, because it could not work optimally.Keywords: Fundamental, Legal Implications, Authority, Investigation, Prosecution Abstrak:Tujuan dari penelitian ini adalah untuk mengetahui implikasi hukum dari hilangnya kewenangan menyidik dan menuntut serta tanggung jawab dari pimpinan KPK. Dalam penelitian ini menggunakan metode penelitian empi ris. Peneliti ini menawarkan suatu hal yang baru, yaitu dilemahkannya lembaga KPK yang berimbas pada kurang optimalnya kinerja pemberantasan korupsi dan bahkan mengakibatkan terhentinya upaya penyelidikan, penyidikan dan penuntutan berbagai kasus korupsi, yang dapat berimplikasi pada dibubarkannya lembaga KPK. Hasil penelitian ini menyatakan bahwa dengan hilangnya kewenangan menyidik dan menuntut serta tanggung jawab pimpinan KPK mengakibatkan menurunnya kinerja KPK, karena tidak dapat bekerja dengan optimal.Kata Kunci: Fundamental, Implikasi Hukum, Kewenangan, Penyidikan, Penuntutan